The Vernacular Literacy Practices of a Newly Literate Moroccan Woman: An Ethnographic Perspective - Reddad Erguig (Journal of Global Initiatives, 2019)
This paper offers a discussion of the literacy practices of a newly literate Moroccan woman. I draw on the social practice theory of literacy and I use ethnographic methods to explore the participant’s life history and offer an account of her family-related literacy practices within the framework of gender studies. In-depth interviews, informal discussion, participant observation, visual ethnography, and documentary photography were employed to collect data over one year. Literacy events were used as the basic unit of analysis and patterns were identified through coding and theme analysis. The findings indicate that the family is a strong impetus for the participant’s literacy acquisition and a major context where she uses the literacy skills she has developed in an adult literacy class. Literacy for this participant is an empowering tool because she has become able to carry out many of the outdoor tasks that were formerly exclusive to men. However, literacy has extended rather than reversed Imane’s home-based roles within her family. These results corroborate the findings of previous research on the embedded nature of literacy practice and illustrate the numerous ways in which the vernacular literacy practices of a participant from Morocco is embedded in a strong gender-based division of labor.